Sustainable hospital accreditation in low- and middle-income countries: lessons for global stakeholders from Sri Lanka's discontinued national program - Dilantha Dharmagunawardene; Mark Avery; David Greenfield; Paula Bowman; Reece Hinchcliff (International Journal of Health Care Quality Assurance, 2026)
Purpose Poor quality and unsafe healthcare exert an immense burden on resource-constrained health systems in Low- and Middle-Income Countries (LMICs). Hospital accreditation programs (HAPs) can help address this challenge, but many programs are not sustained, and limited research explains why. This case study aimed to inform future HAP implementation by examining the emergence, progression and discontinuation of the Sri Lankan Hospital Accreditation Program (SLHAP). Design/methodology/approach Purposively selected accreditation stakeholders (n = 18), directly involved in the SLHAP, were interviewed using a validated, semi-structured guide. Data were thematically analysed, with coding validated. Findings The SLHAP emerged through strong government leadership, with international technical and financial assistance. It progressed through standard practices, including developing standards, surveyor training and compliance gap analysis, facilitated by robust organisational structures. Discontinuation was due to limitations in project management and in the integration of HAP elements, resulting from governance constraints and leadership turnover. This resulted in frequent changes of plans, delays in adapting and communicating standards, and limited awareness and competencies among stakeholders. Practical implications A complex interaction of myriad factors produced the SLHAP's trajectory. The primary factors found to have led to discontinuation (project management, leadership turnover and governance constraints) can be addressed prospectively in other LMICs through comprehensive, effective and long-term project planning and management. Originality/value This study offers an in-depth exploration of meso- and micro-level factors shaping the overall trajectory of SLHAP, highlighting the importance of strengthening project management and meticulous integration of HAP elements. Therefore, SLHAP gives a unique opportunity to learn from a discontinued HAP in an LMIC.